Shopping for Health: Vegetables - Ashley R. Kendall; Wendy J. Dahl (EDIS)
Choosing the right vegetables will help you get the nutrients your body needs every day. With so many choices though, vegetable shopping can seem like a hard task—but it doesn’t have to be. This 4-page fact sheet will help you learn to become a smarter vegetable shopper. Written by Ashley R. Kendall and Wendy J. Dahl, and published by the UF Department of Food Science and Human Nutrition, June 2011. Revised 2018.